Grit Was Associated With Food Insecurity Among Low Income, At-Risk Rural Veterans. (14th June 2022) - Qin, Yue; Sneddon, Douglas; Wadsworth, Shelley MacDermid; Topp, Dave; Sterrett, Rena; Eicher-Miller, Heather
Abstract: Objectives: Rural veterans have poorer health, use health care services less often than their urban counterparts, and have more prevalent food insecurity than average U.S. households. Food insecurity and resource use may be influenced by modifiable psychological attributes such as grit, the determination and perseverance for long-term goals, and help-seeking behaviors, yet no previous studies have evaluated grit and help-seeking among rural veterans. Therefore, the association of grit and help-seeking behavior with food insecurity and use of resources was determined among rural veterans. Methods: Rural veterans from five food pantries in southern Illinois counties with U.S. Department of Agriculture (USDA) rurality scores ≥5 of at least 18 years (n = 176) were recruited from March 2021 to November 2021 for this cross-sectional study. Food security range (USDA 6-item Household Food Security Survey Module), use of resources, grit (Short Grit Scale) and help-seeking behavior (General Help-Seeking Questionnaire) were assessed upon recruitment. Characteristics linked to each outcome variable were determined using chi-square tests. Food security and resource use were compared by grit and help-seeking scores. Regression estimated the relationship between odds of food insecurity and use of resources with grit and help-seeking, with adjustment for covariates. Results: Logistic regression indicated higher grit scores were significantly associated with lower odds of food insecurity (OR = 0.2, p = 0.009). Help seeking was not significant in simple or adjusted regression models. Conclusions: The study provided evidence to inform the content of future educational interventions to improve food insecurity and address health disparities among rural veterans by addressing grit. Enhancement of psychological traits like grit might improve quality of life independently from food security and potentially benefit other aspects of well-being. Funding Sources: McCormick Foundation; Lilly Endowment; Purdue University College of Pharmacy Center for Health Equity and Innovation.